Flora of the Restingasof Sergipe: analysis of the list of indicator species of successional stages (CONAMA Resolution n° 443/2012) - Oliveira, Eduardo Vinícius da Silva; Landim, Myrna Friederichs (Sociedade & Natureza, 2018)
Despite their ecological importance and legal protection status, several types of degradation forms can be observed in Restingaareas along the Brazilian coast. The analysis of legal documents that protect these ecosystems is required in order to make them truly effective. The list of indicator species of Restinga vegetation successional stages in the State of Sergipe (defined by CONAMA Resolution n. 443/2012) was compared with a floristic composition database from Sergipe Restingas, in order to analyze the similarities between them and, hence, the suitability of such legal instrument. The analysis result shows that 52 species (39%) mentioned in the Resolution were not found in Sergipe State Restingasflora database. Among them, nine species showed no collection record in Sergipe and 13 species showed no collection record in the states’ counties located in the coastal plain. The species list provided by CONAMA’s Resolution does not reflect the diversity of Restingasin Sergipe. Therefore, a careful review of the Resolution is required, so it can be used as a more adequate legal instrument for protecting these areas.